Bilateral Ossicular Head Dehiscence Into the Middle Cranial Fossa. (March 2018) - Alvi, Sameer A.; Jones, Joel W.; Lin, Jim
Objectives: To describe a unique case of bilateral dehiscence of the malleus and incus heads into the middle fossa making contact with the temporal lobes, along with its clinical implications. Methods: An analysis of a patient case and review of pertinent literature were performed. Results: A patient with a history of right-sided mastoidectomy for cholesteatoma was evaluated for persistent conductive hearing loss. On computed tomography (CT) and magnetic resonance imaging (MRI), the patient had a complete dehiscence of the tegmen tympani on the right, with ossicular heads being located above the floor of the middle cranial fossa. A similar finding to a milder degree was noted on the left. The patient underwent revision tympanoplasty with mastoidectomy with removal of the incus and ossicular chain reconstruction and middle fossa craniotomy for repair of the right epitympanic dehiscence. Conclusions: We present some of the unique imaging and operative findings involved in an unusual presentation of encephalocele in which the bilateral malleus and incus heads rise above the level of the middle fossa floor.